Magnetic and transport properties of charge ordered La₀.₅Ca₀.₅Mn₀.₃ and La₀.₄Ca₀.₆Mn₀.₃ films - Prokhorov, V.G.; Komashko, V.A.; Kaminsky, G.G.; Lee, Y.P.; Park, S.Y.; Hyun, Y.H.; Svetchnikov, V.L.; Kim, K.W.; Rhee, J.Y. (Физика низких температур, 2006)
The magnetic and the transport properties of La₀.₅Ca₀.₅Mn₀.₃ and La₀.₄Ca₀.₆Mn₀.₃ films with different thickness, prepared by rf-magnetron sputtering by using the so-called «soft» (or powder) target on LaAlO₃ substrate, have been investigated. The electron-diffraction and the high-resolution electron microscopy (HREM) studies show that the charge-ordered phase is observed at room temperature for all films. Both the paramagnetic-to-ferromagnetic transition at TC ≈ 250 K upon cooling and the appearance of an antiferromagnetic (AFM) phase at TN ≧ 140 K were observed in the La₀.₅Ca₀.₅Mn₀.₃ films, while the La₀.₄Ca₀.₆Mn₀.₃ films exhibited the AFM transition only at the same temperature, excepting the small ferromagnetic (FM) response from a «dead» layer. It was shown that the volume fraction of the FM phase in the La₀.₅Ca₀.₅Mn₀.₃ film did not exceed of and the FM phase coexisted with the AFM one at low temperature. All films manifest an exponential temperature dependence of resistance without evidence of the metal-insulator transition. This is explained by the scarcity of the FM phase for the formation of infinite percolating cluster and by an existence of the charge-ordered phase. The field-dependent magnetoresistance at low temperature is described in terms of the spin-assisted polaron-hopping model.